1992
DOI: 10.2105/ajph.82.5.685
|View full text |Cite
|
Sign up to set email alerts
|

The influence of social and political violence on the risk of pregnancy complications.

Abstract: BACKGROUND. Events in Chile provided an opportunity to evaluate health effects associated with exposure to high levels of social and political violence. METHODS. Neighborhoods in Santiago, Chile, were mapped for occurrences of sociopolitical violence during 1985-86, such as bomb threats, military presence, undercover surveillance, and political demonstrations. Six health centers providing prenatal care were then chosen at random: three from "high-violence" and three from "low-violence" neighborhoods. The 161 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 16 publications
3
31
0
Order By: Relevance
“…Inner-city populations that experience high rates of exposure to violence are also characterized by high levels of poverty, hopelessness, lack of opportunity, and unemployment (i.e., chronic ongoing stressors). Living in a violent environment is Grounds Rounds in Environmental Medicine • Wright and Steinbach associated with a chronic pervasive atmosphere of fear and the perceived threat of violence (19,20). Children and families living with community violence are likely to view their world and their lives as being out of their control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inner-city populations that experience high rates of exposure to violence are also characterized by high levels of poverty, hopelessness, lack of opportunity, and unemployment (i.e., chronic ongoing stressors). Living in a violent environment is Grounds Rounds in Environmental Medicine • Wright and Steinbach associated with a chronic pervasive atmosphere of fear and the perceived threat of violence (19,20). Children and families living with community violence are likely to view their world and their lives as being out of their control.…”
Section: Discussionmentioning
confidence: 99%
“…Controlled animal studies consistently demonstrate higher lead levels in iron-deficient animals than in iron-replete controls (18)(19)(20)(21)(22)(23). The mechanism for enhanced absorption is likely to be substitution of Fe +2 with Pb +2 and increased active transport into the body (19,22,24,25).…”
mentioning
confidence: 99%
“…There is also evidence that fatalities in the later stages of pregnancy are negatively related to anemia. See Zapata et al (1992) for more on the relationship between prenatal exposure to violence and pregnancy complications. 17 Table 5 does not include children who were reported to weigh 2500 g at birth in the low-birth-weight category.…”
Section: Number Of Prenatal Visitsmentioning
confidence: 99%
“…Two studies reported associations between urban violence and poor pregnancy outcomes (15,127). In Santiago, Chile, Zapata and colleagues assigned ratings for sociopolitical violence, such as bomb threats, military presence, undercover surveillance, and political demonstrations (127).…”
Section: Quality Of the Environmentmentioning
confidence: 99%
“…In Santiago, Chile, Zapata and colleagues assigned ratings for sociopolitical violence, such as bomb threats, military presence, undercover surveillance, and political demonstrations (127). Collins & David (15) used police department violent-crime statistics to measure urban violence in Chicago's low-income census tracts.…”
Section: Quality Of the Environmentmentioning
confidence: 99%